2016
DOI: 10.1038/srep21302
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic features of binary Li2S-P2S5 glasses

Abstract: The atomic and electronic structures of binary Li2S-P2S5 glasses used as solid electrolytes are modeled by a combination of density functional theory (DFT) and reverse Monte Carlo (RMC) simulation using synchrotron X-ray diffraction, neutron diffraction, and Raman spectroscopy data. The ratio of PSx polyhedral anions based on the Raman spectroscopic results is reflected in the glassy structures of the 67Li2S-33P2S5, 70Li2S-30P2S5, and 75Li2S-25P2S5 glasses, and the plausible structures represent the lithium io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 44 publications
8
110
2
Order By: Relevance
“…On the basis of a previous study 10 , the first peak at around 2.0 Å is related to the P-S correlation associated with the PS 4 tetrahedral anions and has no dependence on the annealing treatment. This means that the PS 4 tetrahedral anions remain in the structure during the crystallization.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…On the basis of a previous study 10 , the first peak at around 2.0 Å is related to the P-S correlation associated with the PS 4 tetrahedral anions and has no dependence on the annealing treatment. This means that the PS 4 tetrahedral anions remain in the structure during the crystallization.…”
Section: Resultsmentioning
confidence: 76%
“…In general, the crystallization of glassy materials results in a decrease in the conductivity 9 , although it increases in a few sulfide glasses owing to the crystallization of a highly conductive new phase 2 . Recently, we reported that 75Li 2 S-25P 2 S 5 glass in the binary Li 2 S-P 2 S 5 system with strongly polarized sulfur has high ionic conductivity 10 . In the sulfide glasses as below reported here, an interesting improvement in the conductivity is observed during annealing, which appears in the glassy phase.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] From the spectra collected, it was observed that the sample hot‐pressed at 270 MPa, E of 28.0 ± 0.6 GPa, showed a ≈20% increase in peak intensity compared to the sample hot‐pressed at 47 and 90 MPa ( E of 16.7 ± 0.6 and 16.5 ± 0.5 GPa, respectively), mostly on the Li–S pairs. This increase is closely related to the change in the coordination environment of the Li ions, [ 25 ] but more importantly, suggesting a more interconnected arrangement between Li and S for the samples hot‐pressed at 180 and 270 MPa resulting in larger elastic constants.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated results were analyzed for trajectories by a DFT-MD simulation at 300 K using the ISAACS program (Le Roux and Petkov, 2010). We determined the experimental data based on the previous work of Ohara et al (2016). Whereas the calculated results show the fluctuations due to our limited sampling, the agreement between our results and the experimental data is good for large values of Q, and the agreement is still good for small values of Q with respect to the positions of maxima and minima.…”
Section: Amorphous Structuresmentioning
confidence: 87%